Home rehabilitation using android-based system as booster on the independences of stroke patients in local government hospital in Aceh, Indonesia - Marlina, Marlina; Imran, Imran; Kurniawan, Ian; Surbakti, Elisabeth (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The independence of stroke patients played the main role in not only preventing the asymptomatic attacks which delayed assistance but also enhancing their quality of life by reducing their dependence on family members or caregivers. However, the inaccessibility and expense of treatment prevented stroke patients from continuing their rehabilitation and exercise after returning home. Thus, the purpose of this study was to provide an efficient system for alternative home rehabilitation to boost the self-care Independence of stroke patients by designing Android-based home rehabilitation. Methods: The quantitative research was conducted using a non-randomized trial where the patients were purposively sampled. 70 participants were joined and divided into two groups: the control and intervention groups. The intervention group will have SIMTROKE application on their smartphone as the home rehabilitation process where control group would not have SIMTROKE installed. The effect of home rehabilitation was assessed by univariate, bivariate analysis and the correlation matrix to analyze home rehabilitation effect to the participants’ self independences. Results: The result showed that the independent intervention in post-stroke patients has a significant effect on increasing the independence of stroke patients to improve their quality of life of stroke patients. The highest improvements were found in urination and toileting followed by defecation, dressing, active and phase motion range, self-care, stepping to stairs, mobilization, showering, and eating abilities. Conclusions: The result proved that home rehabilitation utilizing an Android-based system could be employed as an alternate method to assist stroke patients in improving their independence and quality of life. (www.actabiomedica.it)